Avoiding the Brain Damage - Dueas, Alejandro (JOURNAL OF ADVANCES IN PHYSICS, 2015)
The pursuit of low losses and low distortion are necessary conditions to improve the signal integrity. As mentioned in [1], it is sometimes said that thereare two types of engineers” those who have signal integrityproblems and those who will.As clock frequencies increase,magnifying signal integrityproblems, this saying willbecome even more accurate.On the other hand, the usage of the technology is now a day unavoidable. Thus, to avoid the electromagnetic radiationdirectly on the brain, should be recomendablethe useof the hand off device since the integrated inalambric amplifiers of new generation genertea lot of energy (power). Besides, it is convenient that the user of that technology be aware to the activities he is doing to avoid accidents mainly when he is manipulating some kind of equipment or driving a vehicle.As mentioned in[2], the power amplifier (PA) is a critical component whitin a WLAN transmitter because PA performance affects wireless coverage area, data rate capacity, and battery life.